Ali aur shutar murgh: husnain readers bilingual english & urdu stories (Husnain Lahore, 2020)
Ali and the Ostrich by Husnain Readers is a bilingual story about a curious young boy named Ali who loves animals. One day, he visits a zoo and is fascinated by the ostrich. He learns about its unique features, like its long neck, powerful legs, and the ability to run very fast. The story highlights Ali's curiosity and love for animals, encouraging young readers to explore the wonders of the natural world.